2006
DOI: 10.1001/jama.296.20.2451
|View full text |Cite
|
Sign up to set email alerts
|

Surgical vs Nonoperative Treatment for Lumbar Disk Herniation

Abstract: clinicaltrials.gov Identifier: NCT00000410.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
189
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 643 publications
(202 citation statements)
references
References 22 publications
11
189
1
1
Order By: Relevance
“…There is conflicting evidence on the benefits of surgery for degenerative spine disease, and interpretation of our disparity findings is further complicated by the extensive regional and physician variation in rates of spine surgery. 8184 It is impossible to say if either of the rates of surgery experienced by HIV infected or uninfected patients were appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence on the benefits of surgery for degenerative spine disease, and interpretation of our disparity findings is further complicated by the extensive regional and physician variation in rates of spine surgery. 8184 It is impossible to say if either of the rates of surgery experienced by HIV infected or uninfected patients were appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…These spines underwent MR imaging to determine degeneration grade and T 2 relaxation times (Kerttula et al, 2001; Marinelli et al, 2010; Pfirrmann et al, 2001). The L5-S1 disc was selected for testing because herniations and discectomies are most common at this level (Weinstein et al, 2006). Samples had degeneration grades ranging from 1 to 5 and T 2 relaxation times ranging from 66 to 204, with higher relaxation times indicating healthier discs.…”
Section: Methodsmentioning
confidence: 99%
“…16 Somewhat less definitive conclusions were reported in the Spine Patient Outcome Research Trial, which examined patients who had surgery versus nonoperative treatment for lumbar disc herniation. 17 In this study, it was shown that after 3 months the operated group had greater improvement in terms of bodily pain, physical function, and Oswestry Disability Index. However, these improvements were narrowed after 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 57%